Canopy structure metrics governing stemflow funnelling differ between leafed and leafless states: Insights from a large‐scale rainfall simulator. Issue 8 (13th August 2021) - Iida, Shin'ichi; Wheeler, Kathryn I.; Nanko, Kazuki; Shinohara, Yoshinori; Sun, Xinchao; Sakai, Naoki; Levia, Delphis F.
Abstract: An increasing number of studies have examined the effects of various biotic and abiotic factors on stemflow production. Of those that have ascribed the importance of canopy structure to stemflow production, there has been a bias towards field studies. Coupling Bayesian inference with the NIED (National Research Institute for Earth Science and Disaster Resilience, Tsukuba, Japan) large‐scale rainfall simulator, this study leveraged a unique opportunity to control rainfall amounts and intensities to pinpoint the canopy structural metrics that differentially influence stemflow funnelling ratios for three common tree species between leafed and leafless canopy states. For the first time, we examined whether canopy structure metrics exert a static control on stemflow funnelling ratios or whether different elements of canopy structure are more or less important under leafed or leafless states, thereby allowing us to determine if tacit assumptions about the static influence of canopy structure on stemflow production (and funnelling) are valid (or not). Rainfall simulations were conducted at 15, 20, 30, 40, 50, and 100 mm h −1 under both leafed and leafless tree conditions (12 simulations in total) to detect any differential effects on the presence or absence of foliage on stemflow funnelling ratios. For leafed conditions, the highest percentages of best‐fitting models (ΔDIC ≤2) indicated that stemflow funnelling ratios were mainly controlled by total dry aboveground biomass (Ball ), diameter at breast height (DBH ), total dry foliar biomass (Bf ), tree height (H), and woody to foliar dry biomass ratio (BR). Whilst for the leafless state, the highest percentages of best‐fitting models (ΔDIC ≤2) indicated that total dry branch biomass (Bbr ) was relatively dominant as was the interaction effects between crown projection area and species (CPA:species). These results compel us to reject any assumption of a static effect of different elements of canopy structure on stemflow funnelling. Abstract : Using a large‐scale rainfall simulator, the canopy structural metrics that differentially influence stemflow funnelling ratios were pinpointed for three tree species between leafed/leafless canopy states to examine whether canopy structure metrics exert a static control on stemflow funnelling ratios or whether different elements of canopy structure fluctuate in importance between leafed/leafless states. The canopy structure metrics that influenced stemflow funnelling differed substantially between leafed/leafless states. We reject any tacit assumption of a static effect of canopy structure on stemflow funnelling.